(untitled) (Journal of Student Affairs in Africa, 2021)
South African public higher education has been dogged by student protests since 2015. Many of these disruptions raise pertinent issues for the sector, as well as bring about valued awareness and change. Critical scholars have remarked that in every social or political movement, something of pronounced importance is being said - usually emerging from representatives of groups that have been marginalised, subordinated or even muted. In this article, a "logosemantic" theoretical perspective (Visagie, 2006)1 is utilised to determine some driving conceptualisations emerging in the "languaging strategies" (Stewart, Smith & Denton, 2012) of contemporary student movement culture in South Africa. Not discounting significant research that investigates the impact of the digital age on the communication, mobilisation and sustaining of social movements, this article takes a critical look at grounding concepts that may be identified in the discursive formations of the movements. These are taken to be neither new nor unique, either in essence or manifestation. However, the divisions and polarisations they expose, signal an urgent need for some communicative reform in the "imagined community" (Anderson, 2016) of the academy.